2011
DOI: 10.1108/13552541111156504
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of density measurement techniques for additive manufactured metallic parts

Abstract: Purpose -In the optimisation of processing parameters for additive manufactured parts using, e.g. selective laser melting (SLM) or electron beam melting, the measurement of the part densities is essential and of high interest. However, there is no common standard. Different institutes and system providers are using their own principles and guidelines. This study investigates the accuracies of the three measurement principles: Archimedes method, microscopic analysis of cross sections and X-ray scanning. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 470 publications
(232 citation statements)
references
References 7 publications
4
206
0
Order By: Relevance
“…A comparison of different density measurement methods [8] showed that the repeatability of this method is < 0.1% for high part densities. The minimal scan energy density for high density parts depends on the powder characteristics and the layer thickness [5,6], as shown in Figure 2.…”
Section: Results and Discussion A) Densitymentioning
confidence: 99%
“…A comparison of different density measurement methods [8] showed that the repeatability of this method is < 0.1% for high part densities. The minimal scan energy density for high density parts depends on the powder characteristics and the layer thickness [5,6], as shown in Figure 2.…”
Section: Results and Discussion A) Densitymentioning
confidence: 99%
“…Density determinations are frequently performed using Mettler Toledo AL204 balance by means of Archimedes' principle (buoyancy method) [18,19] at room temperature with the use of n-Butyl acetate (0.88) as a liquid medium, which is also the method used by the density determination kit for balances. Hardness testing of different polyamide samples on top of surface is performed on Rockwell hardness tester, and the specification and other parameters are listed in Table 2.…”
Section: Performance Measuresmentioning
confidence: 99%
“…Part quality, quality assurance Part quality [3][4][5][6] is influenced by the powder material, exposure parameters as well as inert gas flow and temperature at the building platform. Defects like porosity, lack of fusion and rough surfaces can arise if wrong parameters are used.…”
Section: Direct Metal Laser Sinteringmentioning
confidence: 99%